PENGARUH PROMOSI PENJUALAN, IMPULSIVE BUYING BEHAVIOUR PADA KEPUTUSAN PEMBELIAN MAHASISWA SURABAYA MELALUI MEDIA TIKTOK SHOP - Nurul Aisyah; Is Fadhillah (Jurnal Bina Bangsa Ekonomika, 2023)
This study aims to find out more about "The Effect of Promotion and Impulse Buying Behavior on Purchasing Decisions at TikTok Shop." In accordance with the subject matter raised, namely the effect of promotion and impulse buying behavior on purchasing decisions at TikTok Shop among Surabaya city students. The background of this study is the existence of consumer behavior in making a purchase due to the influence of promotions held by a company or business actor and also from consumer impulse buying behavior. The purpose of this study was to determine: how the relationship between the effect of promotion on purchasing decisions at TikTok Shop, to determine the effect of Impulse Buying behavior on purchasing decisions at TikTok Shop, to determine the effect of promotion and Impulse Buying behavior on purchasing decisions at TikTok Shop. The method used in this research is Quantitative method by obtaining data through distributing questionnaires with 100 respondents which were analyzed using SPSS 25. So the conclusions and results obtained from this study are Promotion and Impulse Buying behavior have a significant effect on Purchasing Decisions at TikTok Shop among Surabaya city students